Popular Religiosity in Indonesia Today: The Next Step after âIslam Kulturalâ? - Noor, Farish A. (Al-Jamiah: Journal of Islamic Studies, 2015)
The phenomenon of popular Islam is seen everywhere in the Muslim world today, and expresses itself via a host of means ranging from fashion to architecture as well as new cultural norms that are deemed Islamic. In the case of Indonesia, the expansive growth of the âhalal marketâ--pioneered by Islamic fashion and cosmetics-- has been a powerful variable factor, accounting for the emergence of a new Indonesian Muslim middle-class that has aspirations for upward social mobility as well as social capital. This paper locates the phenomenon of Indonesian pop Islam in the longer and broader history of Indonesia since the time of Suharto to the post-reformasi era of the present, and argues that pop Islam in Indonesia is a serious phenomenon worthy of study; as well as a good indicator of the trajectory of social development in the country. Though not everything that comes under this category may be classified as truly or wholly Islamic, the phenomenon nonetheless points to a growing sense of religious consciousness among the new urban Muslim middle-classes who see themselves as agents of change as well as religio-economic entrepreneurs.[Fenomena Islam popular terlihat di mana-mana di dunia Islam saat ini, dan itu diekspresikan lewat berbagai media seperti tata busana sampai arsitektur, juga termasuk aturan-aturan yang dianggap Islami. Pada kasus Indonesia, perkembangan trend halal-haram yang dimotori oleh dunia tata busana dan kosmetik menyebabkan munculnya kelas menengah baru yang membawa aspirasi itu ke atas sebagai modal. Makalah ini menempatkan Islam popular di Indonesia pada jangka panjang dan luas sebagai fenomena yang layak dijadikan bahan studi; begitu juga arah perkembangan di negara itu. Namun tidak semua di bawah kategori ini masuk dalam wilayah Islamis, namun tetap saja menunjukkan kesadaran keagamaan baru di perkotaan pada kelas menengah yang menganggap dirinya sebagai agen perubahan dan juga penggiat ekonomi agamis].